Determination of usage potential of Hypericum perforatum, Hypericum capitatum, Centaurea cyanus extracts and creams in the cosmetic industry - Ucar, Melis Abahuni; Derun, Emek Moroydor; Pigskin, Mehmet Burcin (YILDIZ TECHNICAL UNIV, 2023)
In recent years, interest in herbal treatments and herbal products has been increasing. Herbal products are preferred because of the properties provided by the secondary metabolites they contain. These products constitute an additional alternative to chemical-added products. Cen-taur y plant is also a popular herb that has been used in the treatment of many diseases for cen-turies. Secondary metabolites such as hyperforin and hypericin in its structure have provided the plant with various qualities such as antibacterial, antidepressant, antioxidant, etc. proper-ties. These properties of the centaury plant have made it a good alternative for skin treatment. Acne scars and blemishes on the skin over time pose a problem for people. Centaury plant will also be a good option for solving such problems. Generally, various studies are carried out on the healing effects of the Hypericum perforatum (Hp) plant on the skin. However, there is limited research on the healing properties of other centaury varieties such as Hypericum capitatum (Hc) and Centaurea cyanus (Cc). There is no study in the literature on formulating a cream composed of combinations of Hp, Hc and Cc herbs. In this study, plant extracts from three centaury species were obtained by soxhlet extraction methods. The hypericin and hy-perforin content of the plant extracts were determined by LC-MS analysis. Creams containing Hc, Hp and Cc extracts and combinations were formulated and antibacterial activities of the creams against Escherichia coli (E.coli) and Staphylococcus aureus (S.aureus) bacteria were de-termined. As a result of the study, 14 placebo cream containing 5% and 15% centaury extracts and 1 non-centaur y extract were produced. It has been concluded that creams containing Cc at 5% and 15% concentrations, Hp at 5% and 15% concentrations, Cc-Hc, Cc-Hp extract in creams can create a potential for use in the cosmetic sector.
Keywords: Herbal Products; Hypericum Perforatum; Hypericum Capitatum; Centaurea Cyanus; Plant Extracts; Cosmetic Industry; VAR. CAPITATUM; HYPERICUM; CONSTITUENTS; Engineering